2017
DOI: 10.1002/pc.24503
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene‐g‐starch nanoparticle biocomposites: Physicochemical properties and biodegradation studies

Abstract: Low density polyethylene‐g‐maleic anhydride‐g‐starch nanoparticle (LMNS) biocomposites have been synthesized in water medium. LMNS biocomposites were fabricated with different starch nanoparticle (NS) loadings (2, 4, 6, 8, and 10 wt%) by compression molding technique. Fourier transform infrared spectroscopy revealed ester linkage between maleic anhydride grafted low density polyethylene (LM) and NS, thereby confirming the improved compatibility of the biocomposites. Thermal analysis confirmed the chemical link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 79 publications
(103 reference statements)
1
5
0
Order By: Relevance
“…In the analyzed case, it can be observed that the change in the roughness of the PE films is similar to the changes in their crystalline structure [ 51 ]. A similar relationship was observed by Sheeja et al [ 91 ]. In the case of the PLA film, its roughness is clearly related to the presence of a filler, which was confirmed by microscopic images ( Figure 2 ) and the photographs taken by the profiler ( Figure 7 ), where spot elevations above the average line were observed.…”
Section: Resultssupporting
confidence: 90%
“…In the analyzed case, it can be observed that the change in the roughness of the PE films is similar to the changes in their crystalline structure [ 51 ]. A similar relationship was observed by Sheeja et al [ 91 ]. In the case of the PLA film, its roughness is clearly related to the presence of a filler, which was confirmed by microscopic images ( Figure 2 ) and the photographs taken by the profiler ( Figure 7 ), where spot elevations above the average line were observed.…”
Section: Resultssupporting
confidence: 90%
“…The static friction coefficient increases with increasing the speed, and the difference between its values obtained with 20 rpm and 40 rpm amounts to 220%. This is probably caused by a higher cooling rate and a higher degree of crystallinity due to more intensive crystallite nucleation [25].…”
Section: Resultsmentioning
confidence: 99%
“…Ltd. L929 mouse fibroblast cells for cell culture were supplied from the National center for cell sciences (India). Starch nanoparticles (NS) have been synthesized according to the literature (Sheeja et al 2017). The detailed procedure has been given in the supplementary data.…”
Section: Methodsmentioning
confidence: 99%